I am the River! Wanda by Zuzanna Orlińska, Literary Tradition and Hydrofeminism - Bednarek, Magdalena (Literatura Ludowa. Journal of Folklore and Popular Culture, 2023)
The paper presents a short story entitled Wanda by Zuzanna Orlińska as a posthumanist reinterpretation of the traditional ethnocentric legend. Subtle changes in te character’s motivation and expanding the plot of Wanda’s story into two other texts create a new understanding of community (not only a national one), as well as a new model of women’s participation in it. The foundations of this new model are agency, care and interdependence.